Associations between serum potassium and adverse clinical outcomes: A systematic literature review. Issue 1 (15th November 2019) - Palaka, Eirini; Grandy, Susan; Darlington, Oliver; McEwan, Phil; van Doornewaard, Alexander
Abstract: Background and objectives: Despite the growing body of evidence characterising the association between serum potassium levels and adverse clinical outcomes, a contemporary summary of available evidence is currently lacking. The objective of this study, therefore, was to undertake a systematic literature review to identify all relevant evidence assessing risk factors associated with the incidence of hyperkalaemia (HK) and also quantifying the effect of serum potassium levels on risk of adverse clinical outcomes. Methods: PubMed (Medline and Medline In‐Process), Embase and the Cochrane Library were searched for studies published between January 2002 and November 2018. Search inclusion criteria included studies describing either the incidence of HK events and any associated risk factors, or associations between HK or serum potassium concentration and adverse clinical outcomes including mortality, hospitalisation, major adverse cardiac events (MACE) and renin‐angiotensin‐aldosterone system inhibitors (RAASi) discontinuation in adult patients with chronic kidney disease (CKD), heart failure (HF), type 2 diabetes (T2DM) or hypertension. Results: The search identified 1, 897 publications. From these, a total of 123 studies met the inclusion criteria and were included in the review. The most commonly identified risk factors associated with HK events were the presence of CKD or renal impairment, T2DM, HF, hypertension, RAASi use and mineralocorticoid receptor antagonist use. Potassium levels both above and below the normal range were consistently associated with adverse clinical outcomes, with relative and absolute risks of outcomes increasing with severity of hyper‐ or hypokalaemia. These associations were consistently reported across a broad range of patient population types and study types. Conclusion: The current body of published evidence is compelling in its confirmation of the associations between serum potassium levels and adverse clinical outcomes. This review further highlights the importance of avoiding both hyper‐ and hypokalaemia, in order to reduce risk of mortality, hospitalisation, MACE and RAASi discontinuation or down‐titration.